Correlation of Cause of Death Issued in Medico Legal Deaths in Hospitals and Cause of Death Found at Autopsy - Shrestha , Kaschev; Neupane , Kabin; Yadav , Yoveen Kumar; Pradhan , Sumee (International Journal of Silkroad Institute of Research and Training, 2024)
Background:The death certificate is essential for legal investigations and public health planning. This study examines theaccuracy of causes of death reported by hospitals versus post-mortem findings and evaluates the completeness of deathcertificates.Method: A prospective, descriptive study was conducted in 99 cases, with hospital-issued death certificates, broughtfor medico-legal autopsy to the Department of Forensic Medicine, Institute of Medicine, Maharajgunj Medical Campus.Cases which were brought dead to the hospital but still were issued with death certificates and cases where the cause ofdeath remained undetermined even after autopsy were excluded. Data was recorded in a pro-forma and analyzed using theSPSS software Version 20.Result: The study involved individuals aged 13 to 30 years, mostly male. Private hospitals issued 66.7% of death certificates,with 55.6% by house officers. Only 62.6% met WHO standards. Autopsies were performed within 24 hours in 67.7% ofcases, revealing blunt force head injury as the leading cause of death (26.3%). There was a 67.7% discrepancy betweenhospital and autopsy causes of death, with house officers and government hospitals showing notable inconsistencies.Conclusion: Factors like the use of standard or non-standard death certificates, the designation of doctors, and the typeof hospital issuing the certificates influence the discrepancies between the causes of death listed by hospitals and thosedetermined after autopsies. This study aims to enhance the existing knowledge on the accuracy of death certificates and islikely the first systematic study of its kind in Nepal, laying the groundwork for future research.